Relationship Between Performance and Commitment Teaching Honorer Economics Teachers - Rosmiati Rosmiati; Zuhri Saputra Hutabarat (Universitas Batanghari Jambi, 2022)
This study aims to determine the results of the analysis of the teaching commitment of honorary teachers in economics at Titian Teras H. Abdurrahman Sayoeti Jambi, to analyze the teaching commitment of honorary teachers in economics at Titian Teras H. Abdurrahman Sayoeti Jambi high school. The teacher's teaching commitment must be considered when the teaching and learning process occurs online or face-to-face. One way to see whether a teacher is committed or not in a school can be seen from the compensation provided by the school, it can be seen from the performance made, and it can even be seen from the teacher's presence when teaching. It is necessary to increase the teaching commitment of teachers in schools to see student progress and to see students' abilities while learning. This type of research is descriptive qualitative research. The informants in this study were all honorary teachers who teach Economics at Titian Teras High School, totaling 2 people. Data collection is done through Observation, Interview, and Documentation. Based on the results of research conducted by researchers on honorary teachers in economics at SMA Negeri Titian Teras H. Abdurrahman Sayoeti Jambi, it can be said that they are committed because seen from their daily work, honorary teachers in economics subjects should be able to increase their teaching commitment.